Comparison of Tube, Gel, and Immunochromatographic Strip Methods for Evaluation of Blood Transfusion Compatibility in Horses. (22nd October 2016) - Luethy, D.; Owens, S.D.; Stefanovski, D.; Nolen‐Walston, R.; Giger, U.
Abstract : Background: Assessment of blood compatibility, typically by tube agglutination (TUBE) and hemolysis crossmatch or, less commonly, by blood typing and alloantibody screening, often is performed before blood transfusion in horses. In contrast, gel column (GEL) and immunochromatographic strip (STRIP) techniques are preferred for compatibility testing in dogs and cats. Objective: To determine the accuracy of novel and standard crossmatch and typing methods. Animals: Thirty‐eight healthy horses, previously blood typed and alloantibody screened. Methods: TUBE and GEL crossmatches were performed on 146 different recipient‐donor pairs with 56 incompatible TUBE crossmatches. Crossmatches were compared by nonparametric area under the curve of receiver operating characteristic (AUC‐ROC) analyses. Horses also were blood typed by the novel immunochromatographic Ca typing STRIP. Results: Compared to TUBE crossmatch, GEL had excellent accuracy for agglutination (AUC‐ROC = 0.903), but marginal accuracy for hemolysis (AUC‐ROC = 0.639). Compared to macroscopic TUBE, microscopic TUBE had excellent accuracy for agglutination (AUC‐ROC = 0.912). The predicted crossmatch compatibility based on blood type and alloantibody assay showed excellent accuracy compared to TUBE and GEL (AUC‐ROC = 0.843 and 0.897, respectively). However, there were more recipient‐donor pairs identified as incompatible by both TUBE and GEL than predicted by blood type and antibody screen, suggesting the presence of unidentified alloantibodies. A Ca typing STRIP exhibited 100% sensitivity and specificity for the 35 Ca+ and 3 Ca‐ horses tested. Conclusions and Clinical Relevance: Gel column crossmatch and Ca typing immunochromatographic strip are simple and accurate methods to evaluate clinical blood compatibility.